2015
DOI: 10.1177/1403494815581696
|View full text |Cite
|
Sign up to set email alerts
|

Body fat in children and adolescents participating in organized sports: Descriptive epidemiological study of 6048 Latvian athletes

Abstract: Almost every fifth child and adolescent participating in organized sports displayed critically low body fat levels. Body fat needs to be assessed regularly in young athletes, to prevent negative consequences on health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
1
8
1
2
Order By: Relevance
“…This tendency is more pronounced in group 1. The results are closely correlated with results of Kalnina et al [6]. In our opinion, this illustrates the effect of intense physical loads on the body.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This tendency is more pronounced in group 1. The results are closely correlated with results of Kalnina et al [6]. In our opinion, this illustrates the effect of intense physical loads on the body.…”
Section: Discussionsupporting
confidence: 91%
“…BIVA is a new technique which has potential in sports and physical exercise. Kalnina et al [6] confirmed the suitability of the bioimpedance method for population studies. Every fifth child in the sport has a reduced level of body fat.…”
Section: Introductionmentioning
confidence: 91%
“…These results differed significantly between the study groups (p £ 0.001). According to the National Scale, %BF for the respective age in young athletes (Kalnina et al, 2015) Intake of minerals and vitamins. The mean of daily intake of minerals and vitamins are shown in Tables 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…Нормы по содержанию жировой массы сравнивали с данными зарубежных исследо-ваний, проведенных с использованием биоим-пендансного анализа в популяции детей и под-ростков, занимающихся и не занимающихся спортом [8,9].…”
Section: материалы и методыunclassified
“…2, 3). В то же время при исполь-зовании норм для детей-спортсменов дефицит жировой массы был выявлен лишь у 5 % в воз-расте 12 лет, у 47 % в возрасте 13 лет и у 10 % [9,[5][6][7][8][9][10][11][12][13][14][15][16]9] 31,9 [30,9] 41,3 [40, 4] в возрасте 15 лет и старше. Данные изменения во многом были связаны с резким скачком ро-ста и увеличением количества мышечной массы 14-15 лет (см.…”
Section: результатыunclassified